Therapy of gastroesophageal reflux disease and functional dyspepsia overlaps with symptoms after usual‐dose proton pump inhibitor: Acotiamide plus usual‐dose proton pump inhibitor versus double‐dose proton pump inhibitor. Issue 3 (22nd February 2018) - Takeuchi, Toshihisa; Takahashi, Yoshiaki; Kawaguchi, Shinpei; Ota, Kazuhiro; Harada, Satoshi; Kojima, Yuichi; Sakamoto, Hiroki; Kuramoto, Takanori; Kojima, Keishi; Sanomura, Makoto; Hoshimoto, Masahiro; Higashino, Takeshi; et al.
Abstract: Background and Aim: Gastroesophageal reflux disease (GERD) and functional dyspepsia (FD) often coexist or overlap. In this study, the efficacy of acotiamide in combination with a standard dose of rabeprazole for GERD and FD was compared with that of a double dose of rabeprazole. Methods: Patients with overlap between GERD and FD experiencing heartburn and epigastric fullness symptoms after standard‐dose proton pump inhibitor (PPI) for ≥ 8 weeks were randomized into two groups and received either acotiamide 300 mg/day + rabeprazole 10 mg/day or rabeprazole 20 mg/day for 4 weeks. Efficacy was assessed by reductions in symptom scores using the Izumo scale questionnaire and modified F‐scale questionnaire. Results: As the primary endpoint, three upper gastrointestinal symptoms (heartburn, epigastralgia, and epigastric fullness) were reduced by ≥ 50% in 40.8% and 46.9% of patients in the combination and PPI double‐dose groups, respectively, with no significant difference between the two groups. Essentially similar results were obtained for the modified F‐scale questionnaire. No serious adverse events were noted. Conclusions: Acotiamide 300 mg/day in combination with rabeprazole 10 mg/day or rabeprazole 20 mg/day relieved symptoms in patients with overlap between GERD and FD experiencing heartburn and epigastric fullness symptoms after standard‐dose PPI for ≥ 8 weeks, and the efficacies did not differ between the two treatments. The combination therapy may be an alternative option for persistent symptoms in these patients.